Mitochondrial Metabolism Modulation: A New Therapeutic Approach for Parkinson's Disease - Arduino, D. M.; Esteves, A. R.; Oliveira, C. R.; Cardoso, S. M. (CNS & Neurological Disorders - Drug Targets, 2010)
Mitochondrial metabolism is a highly orchestrated phenomenon in which many enzyme systems cooperate in a variety of pathways to dictate cellular fate. As well as its vital role in cellular energy metabolism (ATP production), mitochondria are powerful organelles that regulate reactive oxygen species production, NAD+/NADH ratio and programmed cell death. In addition, mitochondrial abnormalities have been well-recognized to contribute to degenerative diseases, like Parkinson's disease (PD). Particularly a deficiency in the mitochondrial respiratory chain complex I and cristae disruption have been consistently described in PD. Moreover, the products of PD-familial genes, including α-synuclein, Parkin, PINK1, DJ-1, LRRK2 and HTR2A, were shown to localize to the mitochondria under certain conditions. It seems that PD has a mitochondrial component so events that would modulate normal mitochondrial functions may compromise neuronal survival. However, it remains an open question whether alterations of these pathways lead to different aspects of PD or whether they converge at a point that is the common denominator of PD pathogenesis. In this review we will focus on mitochondrial metabolic control and its implications on sirtuins activation, microtubule dynamics and the autophagic-lysosomal pathway. We will address mitochondrial metabolism modulation as a new promising therapeutic tool for PD.
Keywords: therapeutic targets